PENGEMBALIAN KERUGIAN KEUANGAN NEGARA DALAM TAHAP PENYIDIKAN TINDAK PIDANA KORUPSI - Kurniawan, Akad Edi (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACT Recovery of state financial losses by efforts to recover state financial losses in corruption crimes in reality still faces obstacles both at the procedural level and at the technical level. At the procedural level, certain legal instruments are needed that are appropriate in accordance with the modus operandi of the crime and the object of the legal problem. In the case of a criminal act of corruption, the results of a criminal act in the form of state finances are in fact not only accepted or enjoyed by the defendant, but also received or enjoyed by a third party who is not a defendant. The formulation of the problem raised is How is the legal arrangement for returning state financial losses in the investigation stage of corruption and how is the Procedure for Returning State Financial Losses in the Implementation Stage of Corruption Crimes.The type of research used is normative juridical research library research with the problem approach used in writing this thesis is the statute approach and field research to obtain data. from corruption. These efforts are regulated in Law Number 31 of 1999 as amended by LAW Number 20 of 2001 concerning Eradication of Criminal Acts of Corruption, Law Number 7 of 2006 concerning Ratification of the United Nations Convention Against Corruption (Anti-Corruption Convention), Law Number 15 of 2002 as amended by LAW Number 25 of 2003 concerning the Crime of Money Laundering (Law on Money Laundering), Law Number 1 of 2006 concerning Mutual Assistance in Criminal Matters and the process of returning state finances in the implementation the case decisions are Asset Search, Confiscation of Assets/Wealth, Prosecution of Compensation Payments and Execution/Implementing Court Decisions Regarding Refund of State Financial Losses Keywords: Corruption, Return of State Finances, Investigation